Anti-inflammatory effect of zerumbone on acute and chronic inflammation models in mice - M.R. Sulaiman; E.K. Perimal; M.N. Akhtar; A.S. Mohamad; M.H. Khalid; N.A. Tasrip; F. Mokhtar; Z.A. Zakaria; N.H. Lajis; D.A. Israf (Elsevier, 2024)
Non-Indexed Publication